The insomnia and suicide link: toward an enhanced understanding of this relationship. (August 2015) - Woznica, Andrea A.; Carney, Colleen E.; Kuo, Janice R.; Moss, Taryn G.
Summary: Despite current knowledge of risk factors for suicidal behaviors, suicide remains a leading cause of death worldwide. This suggests a strong need to identify and understand additional risk factors. A number of recent studies have identified insomnia as a modifiable, independent suicide risk factor. Although a link between insomnia and suicide is emerging, further research is required in order to understand the nature of the relationship. Accordingly, this paper presents an overview of the insomnia and suicide literature to-date, and a discussion of two major limitations within this literature that hinder its progress. First, the classification and assessment of insomnia and suicide-related thoughts and behaviors are inconsistent across studies; and second, there is a lack of empirical studies focused on investigating mediators of the insomnia and suicide relationship. Suggestions are offered within this paper for future studies to address these issues and facilitate new developments in this important research area. Following these suggested lines of research will ultimately inform whether insomnia treatments, particularly cognitive-behavioral therapy for insomnia, can be used to target suicide risk prevention and intervention.